Combine effect of Chondroitinase ABC and low level laser (660 nm) on spinal cord injury model in adult male rats. (October 2017) - Janzadeh, Atousa; Sarveazad, Arash; Yousefifard, Mahmoud; Dameni, Sima; Samani, Fazel Sahraneshin; Mokhtarian, Kobra; Nasirinezhad, Farinaz
Abstract: After spinal cord injury (SCI) there are many recoveries inhibiting factors such as chondroitin sulfate proteoglycan (CSPG) and inflammation. The present study investigated the combinational effect of low level laser therapy (LLLT) as anti-inflammatory agent and Chondroitinase ABC (ChABC) enzyme as CSPG digesting factor on spinal cord after injury. This study performed on 44 male Wistar rats, spinal cord injury induced by a clip compression injury. Animals received two-weeks treatment of 660 nm low level laser (LLL) and intraspinal injection of 1 μg ChABC. Functional recovery, cavity size, myelination, axonal projections around the cavity, fibroblast invasion and expression of glycogen synthase kinase-3β (GSk 3β), CSPG and aquaporin 4 (AQP4) expression were evaluated. In statistical evaluation p < 0.05 considered significant. Result showed the combination of LLLT and ChABC have more effect on reduction of cavity size, improvement of myelination and number of axons around the cavity and decreasing the expression of GSK3β, CSPG and AQP4 expression compared to LLLT and ChABC alone. In the laser and laser + enzyme groups AQP4 expression decreased significantly after SCI. Functional recovery, improved in LLLT and ChABC treated animals, but higher recovery belonged to the combination therapy group. The current study showed combination therapy by LLLT and ChABC is more efficient than a single therapy with each of them. Highlights: Glial scar formation and cytotoxic edema are preventing factors from regeneration after SCI. Early treatment by LLL and ChABC results in reduction glial scar and cytotoxic edema. The combination therapy by LLL and ChABC improved functional recovery.